Effectiveness analysis of single and combined antihypertensive in coronary heart disease patients at Madiun Hospital, East Java - Cahyaningrum, Yanuar As'hari; Febriana, Laela; Putra, R.F.X. Premihadi (Acta Pharmaciae Indonesia, 2024)
Background: Coronary heart disease (CHD) patients frequently require antihypertensive therapy to achieve optimal blood pressure control and reduce cardiovascular complications. The comparative effectiveness of monotherapy versus combination antihypertensive regimens remains an important clinical consideration. Objective: To evaluate the effectiveness of monotherapy and combination antihypertensive treatments in achieving target blood pressure control among hospitalized CHD patients. Methods: This retrospective analysis examined medical records of 139 CHD patients hospitalized between April and June 2021 at a regional hospital in Madiun, East Java. Treatment effectiveness was defined as achieving blood pressure targets below 140/90 mmHg. Independent Sample T-tests compared treatment outcomes between groups. Results: Among 139 patients, 46 received monotherapy and 93 received combination therapy. Monotherapy effectiveness ranged from 80.0% to 88.8%, with calcium channel blockers achieving the highest success rate. Combination therapy demonstrated effectiveness rates between 76.9% and 91.8%, with angiotensin receptor blocker plus calcium channel blocker combinations showing optimal performance. Statistical analysis revealed significant differences in systolic blood pressure reduction between approaches (p=0.000), while diastolic outcomes showed no significant difference (p=0.632). Conclusion: Both treatment approaches demonstrate substantial effectiveness, with combination therapy providing particular advantages for systolic blood pressure management in coronary heart disease patients.